Autism Symptoms, Executive Functioning and Academic Progress in Higher Education Students. - Dijkhuis, Renée; de Sonneville, Leo; Ziermans, Tim; Staal, Wouter; Swaab, Hanna (Journal of Autism & Developmental Disorders, 2020)
Many students with autism spectrum disorders (ASDs) attending higher education drop out prematurely. The predictive value of self-reported daily executive functioning (EF) and (cognitive) performance-based EF (mental flexibility and working memory) for academic progress was evaluated in 54 young adults with ASD (Mage = 22.5, SD = 2.4, 72% male). Regression analyses showed that autism symptom severity explained 12% of variance in academic progress, which was raised to 36% by adding self-reported daily EF, and to 25% by adding performance-based EF. It is suggested that EF is a candidate marker for academic progress in higher education students with ASD and a candidate target for early intervention.